Safety Assessment of Inactivated Whole Virion Booster Vaccine against the SARS-CoV-2 Virus (BelCovidVac) in Immunized Study Subjects aged 18 to 60 Years (day 28) - I. O. Stoma; E. V. Voropaev; E. I. Mikhailova; D. M. Los; O. V. Osipkina; A. Yu. Braga; A. A. Kovalev; A. V. Molchanova; N. V. Trofimova; O. S. Pershenkova; B. S. Yaroshevich; M. N. Mirge (Эпидемиология и вакцинопрофилактика)
Relevance. According to the World Health Organization (WHO), it is not yet possible to effectively stop the spread of new strains of coronavirus [1]. At the same time, most experts and analysts in the field of medicine publicly admit that at the moment vaccination is the most powerful weapon in the fight against COVID-19 [2–6]. While vaccination, like the entire health care system, has now become an element of politics and economics, the creation of proprietary vaccine in each country has become an element of national security [7]. Aims. To evaluate the safety of the inactivated booster vaccine «BelCovidVac» in immunized study subjects from 18 to 60 years old (day 28). Materials and methods. A prospective, randomized, double-blind phase I/II trial evaluated the safety of an inactivated whole virion booster vaccine against the SARS-CoV-2 virus in two doses in healthy study subjects aged 18 to 60 years who had completed a full course of vaccination with the SARS-CoV-2 virus and/or recovered from COVID-19, which included 129 subjects (24 in phase 1 and 105 in phase 2). Results. The study reported 195 adverse reactions in 94 study subjects. The study reported 80 adverse reactions in 24 (100%) study subjects at Phase 1, and 115 adverse reactions in 70 subjects at Phase 2. The study detected mild adverse reactions in 77,50% of cases at Phase 1, and in 71,30% at Phase 2. Moreover, the study found one serious adverse reaction in 1 subject at Phase 2, which occurred as a result of taking placebo. The incidence of adverse reactions with the use of the candidate vaccine in two doses is comparable to placebo (χ2 = 3,15, p = 0,08). Conclusion. The vaccine candidate demonstrated good tolerability at both Phase 1 and Phase 2.